Selective photo-assisted eradication of Triple-Negative breast cancer cells through aptamer decoration of doped conjugated polymer nanoparticles - Ibarra, Luis Exequiel (2022)
Photodynamic therapy (PDT) may be an excellent alternative in the treatment of breast cancer, mainly for the most aggressive type with limited targeted therapies such as triple-negative breast cancer (TNBC). We recently generated conjugated polymer nanoparticles (CPNs) as efficient photosensitizers for the photo-eradication of different cancer cells. With the aim of improving the selectivity of PDT with CPNs, the nanoparticle surface conjugation with unique 2’-Fluoropyrimidines-RNA-aptamers that act as effective recognition elements for functional surface signatures of TNBC cells was proposed and designed. A coupling reaction with carbodiimide was used to covalently bind NH2-modified aptamers with CPNs synthetized with two polystyrene-based polymer donors of COOH groups for the amide reaction. The selectivity of recognition for TNBC membrane receptors and PDT efficacy were assayed in TNBC cells and compared with non-TNBC cells by flow cytometry and cell viability assays. Furthermore, in vitro PDT efficacy was assayed in different TNBC cells with significant improvement results using CL4, sTN29 and sTN58 aptamers compared to unconjugated CPNs and SCR non-specific aptamer. In a chemoresistance TNBC cell model, sTN58 was the candidate for improving labelling and PDT efficacy with CPNs. We proposed sTN58, sTN29 and CL4 aptamers as valuable tools for selective TNBC targeting, cell internalization and therapeutic improvements for CPNs in PDT protocols.